PELAKSANAAN ANALISIS CP ELEMEN GEOMETRI UNTUK MERUMUSKAN TP, ATP, DAN MODUL AJAR PADA FASE E - Kusniawati, Yulia; Purwoko, Riawan Yudi; Astuti, Erni Puji (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
Describe the dormulation of TP and ATP based on the CP geometric elements of Phase E and teaching modules tha show student-centered learnign is the goal of this research. A qualitative research approach was used in this research, collecting data in this research through documentation and interviewing Phase E mathematics teachers. The subject of this research is a matematics teacher Phase E. The data analysis technique used was the data from Miles Huberman which consisted of three activities namely data reduction, presentation, and conclusions. The results of this research show that the CP in Decree of the Head of BSKAP Number 33 of 2022 and the Content Standards for High School Mathematics subjects in Permendikbudristek Number 7 of 2022 are used by teachers to formulate TP, guided by the TP from the driving teacher. This research is focused on geometric elements in Phase E which contains trigonometry material. The CP element geometry is split into four TPs. The TP was compiled together with all math teachers at school to become ATP. Teachers collaborate to arrange material from easy to difficult. The ATP is then held at the MGMP forum to ensure effectiveness and suitability to learning needs. An open module design that can demonstrate student-focused learning is by using the Discovery Learning learning model. Then the teacher also uses discussion methods and peer tutoring.